Implementation Malcom Baldrige for Business MSME Sandals in Wedoro Village - Cakra Wibawa Khoiril Fadli; Eni Purnasari; Ni Wayan Peri Pebriyanti (PT Inovasi Pratama Internasional, 2023)
The purpose of this study is to determine the application of Malcom Baldrige to sandals MSME business in Wedoro village. The method used in this research is a qualitative method based on a phenomenal approach, and is research based on subjective experiences experienced by individuals and logical phenomena. Malcolm Baldrige is a way to comprehensively improve an organization's performance by providing feedback on the organization's overall performance in delivering quality products and services. Malcom Baldrige has criteria (Leadership, Strategic Planning, Customer Focus, Measurement, Analytics, Knowledge Management, Employee Focus, Operations and Performance Focus). In this case, leadership is critical to achieving these seven criteria, as demonstrated by Malcolm Baldrige is top score in his performance evaluation. However, it is not yet clear how Malcolm Baldrige's other six criteria influence leadership. This study is based on the results of interviews and surveys conducted in one of his Sandal MSME is in Wedoro village.